PENTINGNYA PENGELOLAAN MANAJEMEN SUMBER DAYA PENDIDIKAN UNTUK PENINGKATAN PRESTASI SISWA DI SEKOLAH DASAR - Rena Elia (STKIP Subang, 2023)
This research was conducted to see how important educational resource management is to student achievement in elementary schools, because good management will improve student achievement in schools. The purpose of this research is to improve student achievement in learning at school. This study uses a quantitative approach to the type of research is survey research. Survey is a study that takes samples from the population using data instruments in the form of questionnaires, interviews, observations and document data as a means of collecting basic data. The population in this study are teachers and students in elementary schools. With the results of the study showing that the implementation of educational resource management in elementary schools is in the good category based on calculations from several categories carried out in this study, it shows that there is an influence on student achievement at school.